Financial Statement Analysis to Assess Financial Performance Using Financial Ratios at PT.Citra Asri Buana Bogor - Tiyas Lutfiyanti; M.Nur Afif; Yuppy Triwidatin (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to find out how the company's financial performance at PT.Citra Asri Buana Bogor Workshop & Spare Parts from 2017 to 2021 by using financial ratios and to find out the performance of PT.Citra Asri Buana Bogor Workshop & Spare Parts compared to the average standard company industry average. The object in this study is a company engaged in the automotive dealership with subjects related to financial reports in assessing financial performance in the form of financial reports, namely income statements and statements of financial position. The method used in this research is descriptive quantitative. The results of this study on the liquidity ratio, solvency ratio, activity ratio in general are not in good condition while the profitability ratio is in very good condition because every year there are increases and decreases which are still above average. Meanwhile, the results of financial ratios when compared with the industry average standard illustrate that the company is still difficult to compete with other similar companies.